On the control of a non-ideal engineering system: A friction-driven oscillating system with limited power supply - Pontes, B. R.; Oliveira, V. A.; Balthazar, José Manoel [UNESP] (Trans Tech Publications, 2003)
In this work a switching feedback controller for stick-slip compensation of a 2-DOF mass-spring-belt system which interacts with an energy source of limited power supply (non-ideal case) is developed. The system presents an oscillatory behavior due to the stick-slip friction. As the system equilibrium for a conventional feedback controller is not the origin, a switching control law combining a state feedback term and a discontinuous term is proposed to regulate the position of the mass. The problem of tracking a desired periodic trajectory is also considered. The feedback system is robust with respect to the friction force that is assumed to be within known upper and lower bounds.
Keywords: dry friction; limited power supply; non-ideal excitation; nonlinear control; self-excitation